O l??dico no processo formativo de professores e no exerc??cio da doc??ncia - Santos, Camille Anjos de Oliveira (2016)
This research, qualitative, aimed to verify the relevance of the playful in the formation of the pedagogue of Higher Education Institution (HEI) of the Distrito Federal and in the teaching profession in early childhood education and early years of elementary school to enhance the teaching process and full learning. To support theoretical way this research, we sought to understand the playful from its presence in culture, history and education over the years The playful was also regarded as objective activity, exposed in play and play and subjective, revealed as a state of wholeness. Turned up also the history of the formation of the pedagogue in Brazil, the playful presence in the teaching method of many educators and playful teacher training. As data collection instrument was used semi-structured interviews, document analysis and non-participant observation. Participated in the interviews 8 teachers, Faculty of Education graduates of HEI researched, the document analyzed were the Political and Educational Institutional Project, the Educational Project Course of Faculty of Education from the year 2008 and 2010. Three observations in classroom of teachers were made which also responded to the interview, two observations occurred in Early Childhood Education and a 3rd year in elementary school. Concludes that teachers consider important to work with the playful in their formative process, because in practice they need this element to make your student is interested in new knowledge and learn significantly, but the HEI has not considerable space so that the playfulness is a fundamental premise to be worked on teacher training. Indeed, in the teaching profession we determined the presence of playful teaching and the impact of this dimension in the process of teaching and learning.